Pengaruh Likuiditas, Leverage, Profitabilitas, Dan Ukuran Perusahaan Terhadap Manajemen Laba Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2020-2022 - Chintiya Mayliana; Rts Dheby Dwi Thamara; Ratih Kusumastuti (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This study aims to examine the effect of liquidity ratios, leverage ratios, profitability ratios and company size on earnings management of mining companies. This research is a study using a quantitative approach and secondary data sources. The independent variables of this study are the ratio of liquidity, leverage, profitability, and firm size, to the dependent variable of earnings management. With a sample of mining companies that have been listed on the Indonesia Stock Exchange since at least 2020, have issued annual reports ending December 31 and have audited financial reports. The results of this study indicate that there is no influence between the liquidity ratio on earnings management, there is an influence from the leverage ratio on earnings management, there is a positive effect from the profitability ratio on earnings management and there is no effect between firm size and earnings management.